Construction change order management project support system utilizing Delphi method - Naji, Khalid K.; Gunduz, Murat; Naser, Ayman F. (Journal of Civil Engineering and Management, 2022)
Change orders are a major challenge in the construction industry due to the associated time and cost impacts. Thus, managing change effectively assists in alleviating cost overruns and delays. Avoiding change orders and controlling them during project phases requires comprehensive research on the factors affecting the change orders management (COM) performance. This study contributes to existing knowledge by introducing a COM performance measurement framework to help construction professionals evaluate, track, and manage COM performance. A comprehensive literature review, personal meetings, and the Delphi technique are utilized to identify 49 performance factors, categorized into 7 COM groups. 13 Delphi panel members are selected according to purposive sampling technique. The collected data are examined through normality and reliability tests and then analyzed by Spearman’s correlation coefficient, score percentage, and the mean to standard deviation ratio to decide whether to continue with the Delphi method. Consensus between the panelists is reached after the second round of Delphi by the utilization of nonparametric statistical tests. The Delphi study results are followed up by measuring the inter-rater agreement (IRA) and ranking the COM performance factors using the sum rank weighting method. Finally, an operational support system framework that takes into consideration the project life cycle of a project is developed to manage and control these factors to decrease disputes between project parties that occur due to improper COM performance.